Efektivitas LKPD Etnomatematika Budaya Sasak Terhadap Peningkatan Hasil Belajar Siswa Di SMP Negeri 7 Mataram - Citra Ayu, Citra Ayu Afriana; Nyoman Sridana; Ratna Yulis Tyaningsih (Mandalika Mathematics and Educations Journal, 2025)
Mathematics is one of the subjects that plays an important role in everyday life (Elpriska 2018). Mathematics that is related to the experiences and daily life of students can be used as an interesting source of learning. However, in reality, mathematics learning in schools has not maximally achieved its goals (Prasetia, 2016). This study aims to examine the effectiveness of using LKPD learning media based on Sasak cultural ethnomathematics on the learning outcomes of geometry material for eighth-grade students at SMP Negeri 7 Mataram. The research approach used is quantitative with a Posttest Only Control Group Design. The population of this study is all eighth-grade students of SMPN 7 Mataram, and the sampling technique in this research is purposive sampling. The sample examined is eighth-grade students as the control class and VIII-F as the experimental class. The research instruments included test questions and observations. The data analysis techniques used were descriptive and inferential statistical analysis. The learning media used was the LKPD based on the ethnomathematics of Sasak culture. The results of the study indicate that the use of learning media effectively improves the learning outcomes of the geometry material of curved surface shapes for eighth-grade students at SMP Negeri 7 Mataram for the 2024/2025 academic year. This effectiveness is indicated by (1) an increase in the average learning outcomes of the experimental class of 0.8613 which is in the high category; (2) a significant difference in the average math learning outcomes between the control and experimental classes based on the independent sample t-test where t count = 5.861 > 2.005 =